Determinants of rural household poverty in Pakistan with multilevel approach - Sehar Saleem; Maria Aslam; Rehan Ahmad Khan Sherwani; Atif Khan Jadoon; Ambreen Sarwar; Ijaz Butt (Cogent Economics & Finance, 2023)
Rural poverty is often discussed in combination with spatial inequality where rural poor face worse problems with diverse remedies in comparison to urban poor. The present study aims to find out area-level effects and possible determinants of rural poverty based on data from the Rural Household Panel Survey of Pakistan Round-1 (2012). The multilevel binary logistic model is used to integrate concurrent individual and district-level variables to explore area-level effects on poverty. A two-level multilevel model is used for the analysis of the poverty status of 4804 respondents nested in 19 districts. Individual-level variables included in the model are education, socioeconomic status, and spending behaviour. It is found that approximately 60% of individuals of the overall population were found poor, and district-level effect accounts for 7% variations in poverty. A particularly significant ratio of poor is found for people who attained deeni madrassa/religious education or no education at all. Poverty existence is significantly associated with spending behavior and socioeconomic status. The persons with relatively middle/high socioeconomic status and successful educational achievement but a lacking attitude toward spending money are considered poor.
Keywords: A14; I31; I32; P46; 330; district-level effects; education; multilevel logistic regression; poverty